Combined incubation of Cadmium, docosahexaenoic and eicosapentaenoic acid results in increased uptake of cadmium and elevated docosapentaenoic acid content in Hepatocytes in vitro. Issue 1 (December 2015) - Linhartova, Pavla; Sampels, Sabine
Abstract Background Human hepatocellular cells Hep G2 were used to mimic and investigate the effect of the intake of cadmium (Cd2+ ) contaminated fish on cytotoxicity, fatty acid (FA) and phospholipid class composition. Methods Cells were incubated with a combination of Cd2+ and eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) fish specific FA. Results We measured a significant increased proportion of EPA and DHA in the treated cells compared to the control line confirming the uptake. While doses of 25 μM DHA showed to be toxic to the cells, repeated short term incubations (2 h) at lower doses resulted in an increased uptake of DHA. The resarzurin assay, evaluating cell viability, showed a significant decrease in cell viability between Cd2+ incubation time and, further, the pre-incubation with BSA-FA complex resulted in significantly increased cell viability. On the metabolic level, increased concentrations of EPA and DHA resulted in an increased proportion of docosapentaenoic acid (DPA) which indicated an increased metabolism. Also 24-h combined incubations of 5 μM Cd2+ and EPA and DHA showed a significant increase DPA in the total lipid fraction of the cells. In addition, incubation with 5 μM Cd2+ for 24 h also decreased the total cardiolipin (CL) fraction from the identified phospholipids. Conclusions We confirmed that the applied FA were taken up by the cells. A combination of EPA, DHA and Cd2+ influenced lysosomal integrity, cell viability and lipid metabolism in the cells. The most important finding is that DHA and EPA reduced the detrimental effect of Cd2+ on cell viability. The exact effects and kinetics behind our observations still need further evaluation.